The Kepler Giant Planet Search. I. A Decade of Kepler Planet-host Radial Velocities from W. M. Keck Observatory - Lauren M. Weiss; Howard Isaacson; Andrew W. Howard; Benjamin J. Fulton; Erik A. Petigura; Daniel Fabrycky; Daniel Jontof-Hutter; Jason H. Steffen; Hilke E. Schlichting; Jason T. Wright; Corey Beard; Casey L. Brinkman; et al. (The Astrophysical Journal Supplement Series, 2023)
Despite the importance of Jupiter and Saturn to Earth’s formation and habitability, there has not yet been a comprehensive observational study of how giant exoplanets correlate with the architectural properties of close-in, sub-Neptune-sized exoplanets. This is largely because transit surveys are particularly insensitive to planets at orbital separations ≳1 au, and so their census of Jupiter-like planets is incomplete, inhibiting our study of the relationship between Jupiter-like planets and the small planets that do transit. To investigate the relationship between close-in, small and distant, giant planets, we conducted the Kepler Giant Planet Survey (KGPS). Using the W. M. Keck Observatory High Resolution Echelle Spectrometer, we spent over a decade collecting 2844 radial velocities (RVs; 2167 of which are presented here for the first time) of 63 Sunlike stars that host 157 transiting planets. We had no prior knowledge of which systems would contain giant planets beyond 1 au, making this survey unbiased with respect to previously detected Jovians. We announce RV-detected companions to 20 stars from our sample. These include 13 Jovians ( $0.3\,M_{{\rm{J}}}\lt M\sin i\lt 13\,M_{{\rm{J}}}$ , 1 au < a < 10 au), eight nontransiting sub-Saturns, and three stellar-mass companions. We also present updated masses and densities of 84 transiting planets. The KGPS project leverages one of the longest-running and most data-rich collections of RVs of the NASA Kepler systems yet, and it will provide a basis for addressing whether giant planets help or hinder the growth of sub-Neptune-sized and terrestrial planets. Future KGPS papers will examine the relationship between small, transiting planets and their long-period companions.